Model Pembangunan Inkubator Wirausaha Syariah Perguruan Tinggi di Palembang - John Roni Coyanda (Penerbit Goodwood, 2021)
Entrepreneurship has existed since ancient times, and the Prophet Muhammad ? exemplified business, buying and selling, and expanding business opportunities. Economic development has as one of its objectives the provision of employment opportunities to anticipate labor force growth that exceeds job opportunities and creates new job opportunities. Some factors determine this. To begin, population growth is typically greater than capital growth. Second, the demographic profile is younger, which means that a more significant number of people are entering the workforce. Thirdly, the industrial structure, which is characterized by a lack of economic diversification and an insufficient level of population skills. Additionally, entrepreneurial activity is still low, and new young businesses have not been particularly active in starting a business opportunity that can be created and run after they graduate from college, which has an effect on a country's level of entrepreneurial growth among youth.